The mercantilist index of trade policy - Anderson, James E. 1943-; Neary, J. Peter 1950- (NBER working paper series, 1999)
This paper develops and characterizes an index of trade policy restrictiveness defined as the uniform tariff equivalent which maintains the same volume of trade as a given set of tariffs, quota, and domestic taxes and subsidies. We relate this volume-equivalent index to the Trade Restrictiveness Index welfare-equivalent measure changes in the generalised mean and variance of the tariff schedule. Applications to international cross-section and time-series comparisons of trade policy show that the new index frequently gives a very different picture than do standard indexes.